Continuous thermosalinograph oceanography along RV ALKOR cruise track AL588 - Michael Schlundt; Steffen Funk; Anton Höper (PANGAEA, 2024)
Underway temperature and salinity data was collected along the cruise track with a thermosalinograph (TSG) together with a SBE38 Thermometer. Both systems worked throughout the cruise. While temperature is taken at the water inlet in about 4 m depth, salinity is estimated within the interior TSG from conductivity and interior temperature. No temperature and salinity calibration was performed. For details to all processing steps see Data Processing Report.